Using The Laws Of Physics In Life Situations - Tatyana Alekseyevna Orlova; Muniraxon Ergasheva (Genius Journals, 2025)
Physics plays a key role in explaining the phenomena we encounter daily, from the motion of cars to the operation of our smartphones. Modern technologies largely depend on discoveries in the field of physics. This article highlights not only the importance of physical laws in everyday life but also the role of continuous education in their study and application.
Keywords: Physics; everyday life; physical laws